Tilt - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2012)
Three teens, connected by their parents' bad choices, tell in their own voices of their lives and loves as Shane finds his first boyfriend, Mikayla discovers that love can be pushed too far, and Harley loses herself in her quest for new experiences.
Keywords: Novels in verse; Dating (Social customs) -- Fiction; Love -- Fiction; Family problems -- Fiction; Family life -- Nevada -- Fiction; Dating (Social customs) -- Fiction; Family life -- Nevada -- Fiction; Nevada -- Fiction; Nevada -- Fiction; Romance fiction